Penerapan Strategi Pembelajaran dalam Materi Praktik Penjas pada Masa Pandemi di SMP Negeri se Kecamatan Temanggung (Indonesian Journal for Physical Education and Sport, 2023)
The problem of this research is how to apply learning strategies in Physical Education practice material during the pandemic at State Junior High Schools throughout the Temanggung District. Objectives through the application of learning strategies. Descriptive qualitative research method. Data analysis uses data reduction, data presentation, concluding. The results of the study are online according to the pandemic period. The results of the study concluded that the application of learning strategies in physical education practice material during the pandemic was still not by basic competencies, especially in guided practice material, it still seemed less well implemented due to certain obstacles